THE APPLICATION OF THE PRINCIPLES OF MARKETING AND LOGISTICS FOR THE IMPLEMENTATION OF THE NEW SERVICE ON PASSENGER RAILWAY TRANSPORT - Melnyk, T. S.; Loboiko, L. M.; Khrystofor, O. V. (Science and Transport Progress, 2008)
In the article the marketing research of conditions of introduction of a new service in the field of passenger service on the railway transport is presented, the organizational aspects of its providing on the base of application of logistic principles of management by stream processes are determined.